(untitled) (Indian Journal of Experimental Biology (IJEB), 2022)
Aspergillus sp. is widely distributed in nature and plays significant roles in the degradation of lignocellulose biomass and extensively used in bioprocess and fermentation technology and many species are also a generally regarded safe. Many of the Aspergillus species are established cell factories due to their inherent capacity in secreting large number of hydrolytic enzymes. With the advent of next generation genomic technologies and metabolic engineering technologies, the production potential of Aspergillus cell factory has improved over the years. Various genome editing tools has been developed for Aspergillus like engineered nucleases, zinc finger nucleases, TALEN and CRISPR-Cas9 system. Currently, the CRISPR/Cas9-based technique is extensively used to enhance the effectiveness of gene manipulation in model system Aspergillus nidulans and other strains like Aspergillus oryzae, Aspergillus niger and Aspergillus fumigatus. This review describes the recent developments of genome editing technologies in Aspergillus the synthesis of heterologous proteins and secondary metabolites in the Aspergillus species.